De Belo Horizonte a Confins: a reconfiguração espacial metropolitana e a tipicidade do lugar - Pereira, Grasieli Adriana Souza (2011)
The metropolis is a dynamical and complex area, which important role played by it is to meet demands for services, trade, education and infrastructure. The expansion of the metropolis becomes a concern of many scholars, since it is directly linked to the growth of smaller cities, which can still be affected by the proliferation of slums and the lack of infrastructure, dscharacterizing the livelihood of small cities, which enables emergence of new territoriality. The need for new areas to permit the urban growth led to the metropolitan city of Belo Horizonte to the city of Confins to start the construction project of the Tancredo Neves International Airport, in the 1980s. This factor has led to many political conflicts and environmental problems due to the distance of the airport in relation to the metropolis and as a region in which predominates the karst relay. However, despite of these adversities, the Airport was achieved. The study area of this work is located in the north of the capital, the city of Confins, where is installed the Tancredo Neves International Airport. This region tends to introduce a new dynamism with important implications and consequences on the livelihood of residents, triggered by the urbanization process that focused on site. New government projects targeted to this region are being planned and executed, as the creation of a road network to facilitate access to the airport and the proposition of creating a technology park. The goal is to study the influence of the construction of this urban equipment in the small town of Confins. For this, we intend to highlight the specificities of the place, consider the lifestyle of the urban population and the improvements resulting from the government and private investments deployed in the city. The rationale of this study is based on a lack of specific work related to the municipality of Confins and the influence to the development of the place. It is understood that in this case, the process of urbanization is represented by a dynamic metropolis, thus, understanding the urban dynamism contributes to the analysis and discussion of issues of the place and more than that, for the formation of a meaning on the development of small towns through the construction of important works for the integration and development of the country.